Kak povysit' sorevnovatel'nuyu nadezhnost' vysokokvalifitsirovannykh bortsov - Bleyer, A. N. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
This study was undertaken to determine the ways of the competitive reliability`s improvement in wrestlers of the Grecian-Roman Style. As a result of the research it was found that the physical fatigue progressing during match leads to decrease of the competitive activities`es indices, that the competitive reliability of wrestlers in tactical-technical actions is determined by the dynamics of the taking position time`s index. It is offered a suitable from of training work.